Commitment to an entrepreneurship training programme for self-employed entrepreneurs, and learning from participation - Lenita Nieminen; Ulla Hytti (Emerald, 2022)
Purpose To explore how self-employed entrepreneurs commit themselves to an entrepreneurship training programme and how such commitment relates to their perceptions of learning.
Methodology The data were collected through qualitative, inductive methods by interviewing and observing six entrepreneurs who took part in an entrepreneurship training programme.
Findings The study reveals that entrepreneurial activities and a strong attachment to entrepreneurship may detach entrepreneurs from an entrepreneurship community. Generally, participants appreciated the social aspect of learning, peer support and confidence-building provided by the programme and the learning community. Nevertheless, the participation was a double-edged sword: it allowed those who were not active in entrepreneurship to explore entrepreneurship, but for those who were active in entrepreneurship and in professional communities, their participation represented a potential liability and a threat to their image as a credible entrepreneur.
Research implications More research is needed on the social aspect related to training programmes, particularly focusing on potential adverse outcomes, such as over-embeddedness in the community.
Practical implications Training programme organizers could benefit from understanding the social aspects of learning in emphasizing the role of peer support but also of the potential negative aspects of socializing.
Originality/value Our study offers insight into the relationship between commitment and learning in micro firms, and it contributes to a deeper understanding of the way community and social relationships facilitate or impede learning by self-employed entrepreneurs. There is a risk that the social aspect of peer support and the community replaces entrepreneurs’ need to ‘go out there’ and expose themselves to learning from experience.
Keywords: commitment, community of practice, learning, participation, self-employed